Study on Root Hydraulic Lift of Drought-Tolerant and Drought-Sensitive Potato Cultivars (Solanum tuberosum L.) - Zhao, H.; Li, Y.; Ali, K.; Zhang, C.C.; Qin, T.; Bi, Z.; Liu, Y.; Liu, Z.; Kear, P.; Sun, C.; Bai, J. (MDPI, 2023)
: In order to investigate the relationship between hydraulic lift and drought tolerance in potato, four cultivars differing in drought susceptibilities were selected, and a pot experiment with three different irrigation conditions was carried out in a randomized complete block design. Under irrigation conditions (WW), hydraulic lift of soil water was not observed in the upper pots. Under halfirrigation (DW) and drought (DD) conditions, the water content increased in the upper pots, along with a change in root-related traits, higher biomass, and lower proline (Pro) and malondialdehyde (MDA) concentrations observed in the drought-tolerant cultivars (Longshu NO.3 and Xindaping), whereas the drought-sensitive cultivars (Favorita and Atlantic) had contrary results. As the degree of drought stress increased, the phenomenon of hydraulic lift was inhibited completely, along with a reduction in soil water content and biomass and an increase in Pro and MDA accumulation. Genotypes of Longshu NO.3 and Xindaping exhibited higher tolerance to drought stress than Favorita and Atlantic under drought conditions. In addition, similar results were also obtained for the determination of plant height, leaf water content, root activity, and root–shoot ratio. This study revealed that there was a phenomenon of hydraulic redistribution among different potato cultivars, along with hydraulic lift strongly associated with the root growth, biomass allocation, and other physiological traits that potentially confer drought resistance.